Application of a Realistic Mathematical Approach to Improve Students' Mathematical Literacy Ability - Dwigita Melani Christina Limbong; Elvis Napitupulu (Formosa Journal of Multidisciplinary Research, 2023)
This study aims to describe how students' mathematical literacy skills increased after applying a realistic mathematics approach in Class VIII-2 of SMP Negeri 4 Medan. The subjects in this study were 30 students in class VIII-2 at SMP Negeri 4 Medan and the object of this study was to increase students' mathematical literacy skills through a realistic mathematics approach. The research instruments used were tests and reflective journals. This research is a classroom action research that lasted for two cycles. The results of data analysis were obtained from the results of tests of students' mathematical literacy abilities which increased from cycle I to cycle II after applying a realistic mathematics approach. In cycle I, an average score of 63.05 was obtained in the low category, classical completeness was 26.6% and the N-Gain value was 0.5 in the medium category. The data shows that the score indicators have not met the target, so the research is continued in cycle II by making improvements from cycle I. In cycle II, an average score of 82.5 is obtained in the high category, classical completeness is 86.6% and the N-Gain value of 0.8 with the high category. These data indicate that the value indicators have met the target so that the research was stopped. So, based on the results of this study, the mathematical literacy ability of class VIII-2 students of SMP Negeri 4 Medan can be increased by using a realistic mathematics approach.